FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI DALAM KEHAMILAN DI UPTD PUSKESMAS BURNAI MULYA KABUPATEN OKU TIMUR TAHUN 2024 - Nengah Suriyani; Bina Aquari; Wahyu Ernawati; Sri Handayani (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2025)
Background: Hypertension in pregnancy is one of the leading causes of maternal and fetal mortality worldwide. The World Health Organization (WHO) reports that hypertension accounts for approximately 12–14% of total maternal deaths globally. Factors such as knowledge, maternal age, and history of hypertension are important determinants in the occurrence of pregnancy-induced hypertension. Objective: This study aims to investigate the relationship between knowledge level, age, and history of hypertension with the occurrence of hypertension in pregnant women at the UPTD Burnai Mulya Health Center in OKU Timur District in 2024. Method: This is a quantitative study with a cross-sectional design. The population consisted of 190 pregnant women, and a sample of 57 individuals was selected using non-random sampling. Data analysis was performed using the Chi-Square test with a significance level of p<0.05. Results: Among the 30 respondents with poor knowledge, 66.7% experienced hypertension (p=0.000). Among the 35 respondents in the high-risk age group, 51.4% experienced hypertension (p=0.012). Among the 28 respondents with a history of hypertension, 67.9% experienced hypertension (p=0.000). There was a significant association between the three variables and the occurrence of hypertension. Conclusion: Level of knowledge, high-risk age, and history of hypertension were significantly associated with the occurrence of hypertension in pregnant women. It is recommended that midwives be more proactive in providing education and regular blood pressure monitoring to prevent pregnancy complications.